2017
DOI: 10.1152/japplphysiol.00995.2016
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of middle cerebral artery blood flow velocity during moderate-intensity exercise

Abstract: The dynamic response to a stimulus such as exercise can reveal valuable insights into systems control in health and disease that are not evident from the steady-state perturbation. However, the dynamic response profile and kinetics of cerebrovascular function have not been determined to date. We tested the hypotheses that bilateral middle cerebral artery blood flow mean velocity (MCA) increases exponentially following the onset of moderate-intensity exercise in 10 healthy young subjects. The MCA response profi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
138
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 65 publications
(150 citation statements)
references
References 67 publications
10
138
2
Order By: Relevance
“…10,11 Quantitative measurement of cerebral blood flow at rest provides valuable steady state information. However, examining the dynamic response, CVR, from rest to moderate intensity exercise can provide unique information regarding cerebrovascular control mechanisms 29 especially in a well-characterized cohort. All of our participants were sedentary 26 and were classified as moderate or high cardiac risk.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…10,11 Quantitative measurement of cerebral blood flow at rest provides valuable steady state information. However, examining the dynamic response, CVR, from rest to moderate intensity exercise can provide unique information regarding cerebrovascular control mechanisms 29 especially in a well-characterized cohort. All of our participants were sedentary 26 and were classified as moderate or high cardiac risk.…”
Section: Discussionmentioning
confidence: 99%
“…26 The laboratory room for the experimental session was dimly lit, quiet, and temperature maintained between 22 and 24 C. 27,28 External stimuli were kept to a minimum during the testing session. 29 The left MCA was used for the transcranial Doppler (TCD) ultrasound with a 2-MHz probe (RobotoC2MD, Multigon Industries) placed over the temporal window and fixed in place using a robotic TCD headpiece. If the left MCA was not obtainable, then the right side was used.…”
Section: Transcranial Dopplermentioning
confidence: 99%
“…It has been proposed that the cognitive benefit from exercise may be associated with the acute, exercise-related increase in cerebral blood flow (Ogoh, 2017). Leg-based dynamic exercise, such as cycling (Jorgensen et al, 1992;Hellstrom et al, 1996;Ogoh and Ainslie, 2009), recumbent stepping (Billinger et al, 2017), and treadmill running (Jiang et al, 1995) increase cerebral blood velocity (CBV) through the independent and interactive factors involved in cerebral blood flow regulation (e.g., blood pressure [BP], cardiac output, and alterations in arterial CO 2 ; Ide andSecher, 2000, Ogoh andAinslie, 2009). Furthermore, upright leg-based, aquatic exercise has recently been shown to augment the increase in CBV compared to intensity-matched land exercise (Parfitt et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Another potential mechanism known to influence CBF is partial pressure of carbon dioxide (PaCO 2 ) in the arterial blood. As discussed in our prior work, we acknowledge that P ET CO 2 is not identical to PaCO 2 (Billinger et al ), but we can expect an approximate 3–5 mmHg increase in P ET CO 2 from rest to moderate‐intensity exercise. We observed a consistent increase in P ET CO 2 from rest to exercise at all study visits.…”
Section: Discussionmentioning
confidence: 63%
“…We published a novel method for measuring cerebrovascular response to a change in demand from rest to moderate‐intensity exercise in the middle cerebral artery (MCA) (Billinger et al ). The resolution of the MCA velocity (MCAv) kinetics provided unique information for age‐ and sex‐differences and revealed that the kinetics profile was blunted in older adults when compared to their younger counterparts (Ward et al ).…”
Section: Introductionmentioning
confidence: 99%